Thermally enhanced pristine polyolefins: fundamentals, progress and prospective - A.U. Chaudhry (17075308) (2020)
The low thermal conductivity of polymers hinders their use in applications requiring high thermal conductivity such as electronic packaging, heat exchangers, and thermal management devices. Polyethylene and polypropylene (polyolefins) account for ∼55% of the global thermoplastic production. Improving the thermal conductivity of this class of thermoplastics is important for many applications. This comprehensive review analyzes the advances on enhancing the thermal conductivity of pristine polyolefins. First, the mechanism of thermal transport in polymers and the key parameters that govern conductive heat transfer through polymers are discussed. Moreover, the progress in modeling and simulation of thermal conductivity of polyolefins are analyzed. Furthermore, the different approaches to enhance the thermal conductivity of polyolefins through controlling their microstructure, crystallinity and chain orientation are presented. Finally, the key challenges and prospective directions for developing thermally enhanced pristine polyolefins are outlined. Other Information Published in: Journal of Materials Research and Technology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jmrt.2020.07.101